From South to North in the globalised world of early childhood education and care: varied national and local responses in selected countries - Branislav Pupala; Ondrej Kaščák (Charles University, 2020)
This article analyses the neoliberal transformation of ECEC in five selected countries (Germany, Slovakia, Indonesia, Nepal, and Kenya). Both the Global South and the Global North are represented. The countries were selected either because of the authors' involvement in research in the respective country or because of their long-term personal experience of that particular system of ECEC. The knowledge the authors acquired enabled them to delve deeper into the question of the point at which ECEC systems encounter neoliberal education policy and to describe the different ways in which the countries have adapted to the new policies. The article shows that neoliberal education policies require different types of adaptation and that these may have very different effects on the system of ECEC - from a change in concept to system convergence and practical resistance or total governance of the ECEC sector. The article contributes to a more granular understanding of the effect of the economising discourse on the ECEC sector. Keywords: ECEC, social investment approach, EU, Germany, Slovakia, Indonesia, Kenya, Nepal, Global North, Global South